En polakk i norsk fortid. Om feil de polskspråklige norskinnlærerne gjør i bruk av perfektum og preteritum - Janik, Marta Olga (Folia Scandinavica Posnaniensia, 2010)
The following paper proves that crosslinguistic influence is the cause of mistakes made by Polish learners of Norwegian as a second language (L2) in their use of Norwegian tenses: perfektum and preteritum. The mistakes seem to be characteristic only for Polish L2 users of Norwegian and not necessarily for other (at least English and German) L2 users of the language. The paper also mentions some factors which affect the occurrence of transfer. As a conclusion, some arguments are proposed for classifying the transfer as conceptual.